2011
DOI: 10.1063/1.3617462
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, flexible, ultrathin sound source devices using Indium Tin oxide films

Abstract: Thermoacoustic effects were observed in 100-nm indium tin oxide (ITO) films. The sound emission from the ITO films was measured as a function of power, distance, and frequency. Significant flat and wide frequency responses occurred between 20 and 50 kHz. The sound pressure and efficiency were in good agreement with theoretical results. This indicates that a thermoacoustic effect exists in metal-oxide materials and that a large family of transparent electrode materials may exhibit similar properties. Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…Such plateaus at high frequencies are characteristic of thermophones and were first observed by Shinoda et al [7]. This change in behavior usually attributed to near field interference [17] or heterogeneous substrates, whether in the form of multiple layers [7,11,8] or air domains [13], but neither of these are present in our thermophone.…”
Section: Modeling Sound Emissionmentioning
confidence: 64%
See 1 more Smart Citation
“…Such plateaus at high frequencies are characteristic of thermophones and were first observed by Shinoda et al [7]. This change in behavior usually attributed to near field interference [17] or heterogeneous substrates, whether in the form of multiple layers [7,11,8] or air domains [13], but neither of these are present in our thermophone.…”
Section: Modeling Sound Emissionmentioning
confidence: 64%
“…Then in 2008, Xiao et al [16] demonstrated that freestanding films of carbon nanotubes (CNTs) could function as thermophones and be transparent, flexible, and stretchable. [16] This work directed attention towards other types of films composed of metals, [7] graphene, [8] indium tin oxide (ITO)-coated glass, [11] and the electronically conductive polymer PEDOT (poly (3,4-ethylenedioxythiophene)). [9] The objective of our work was to characterize the properties of ultra-long (mm scale) polycrystalline gold nanowires as thermophones.…”
Section: Table Of Contentsmentioning
confidence: 99%
“…4 However, organic material in an acoustic application has not been reported. Recent work reported the application of metal, 5-9 carbon nanotube, [10][11][12][13] graphene, 14 and indium tin oxide 15 in the acoustic field. Inspired by such work, we propose the design of an organic sound-emitting device (SED) and investigate its acoustic properties.…”
mentioning
confidence: 99%
“…Thus 20-30 nm thin and transparent airborne ultrasound emitters can be built and embedded in the screens of smart phones, tablets and other electronic devices [15].…”
Section: Introductionmentioning
confidence: 99%